America's uncivil wars : the sixties era : from Elvis to the fall of Richard Nixon - Lytle, Mark H. (Oxford University Press, 2006)
Employs a chronological narrative to identify three distinct phases during which events of the era unfolded. This book captures the sweep of this tumultuous era, analyzing both the cultural and political influences on the movements of the 1960s. It brings a fresh approach to our understanding of not only the 1960s but also US history since 1945.